Synovial cell sarcoma of the pleura: an uncommon cause of a haemorrhagic pleural effusion - Choudhary, C. R.; Desai, Govind; Verma, Lokesh; Yogi, Suresh Kumar (International Journal of Advances in Medicine, 2020)
Soft tissue tumors account for a small percentage of malignancies and synovial sarcomas account for 10% of soft tissue tumors in our body, among them are the synovial sarcomas (SS).These arise from various sites and are of mesenchymal origin, Primary pleural synovial sarcomas are very rare tumours and account for not more than 0.5% of lung malignancies, they are being diagnosed mainly by the immunohistochemistry and classical cytogentic translocation t(x;18). This tumor has no sex preference and is commonly seen in the age group of 30-45.Our case is of a elderly male with massive pleural effusion who was diagnosed as having biphasic variant of synovial sarcoma of pleura by the help of immunohistochemistry. Treatment is mainly surgical resection and chemotherapy with ifosfamide/ adriamycin or radiotherapy. It must be considered as differential for biopsy proven malignant mesothelioma and hence immunohistochemistry should be must for all biopsy proven mesotheliomas.